2020
DOI: 10.1055/a-1145-3500
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Barrett’s esophagus in obese patients undergoing pre-bariatric surgery evaluation: a systematic review and meta-analysis

Abstract: Introduction Obesity is a known risk factor for gastroesophageal reflux disease (GERD), Barrett’s esophagus (BE), and esophageal adenocarcinoma (EAC). Obese patients routinely undergo preoperative esophagogastroduodenoscopy (EGD) before bariatric procedures. We aimed to assess the prevalence of BE in this patient population. Methods We conducted a comprehensive literature search ending in March 2019. Search results were imported into covidence.org and screened by two independent reviewers. Heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Note that 11.6% of cases were de novo; none of the patients who had SG had BE at the screening EGD before the procedure. In our previous meta-analysis, 13 we studied more than 13,000 patients who had EGD before bariatric surgery and showed that despite their obesity, the risk of BE in this patient population was low (<1%). The above data would suggest that screening might be more useful if started around 3 years after SG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that 11.6% of cases were de novo; none of the patients who had SG had BE at the screening EGD before the procedure. In our previous meta-analysis, 13 we studied more than 13,000 patients who had EGD before bariatric surgery and showed that despite their obesity, the risk of BE in this patient population was low (<1%). The above data would suggest that screening might be more useful if started around 3 years after SG.…”
Section: Discussionmentioning
confidence: 99%
“…18 The final score for studies (with a maximum score of 16) was reported, as previously described. 13 Based on this system, we rated studies as high (12)(13)(14)(15)(16); moderate (9-11); fair (7-8), and poor ( 6). We also planned to identify and remove possible outliers.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial version of the study was conceptualized based on our experience in conducting systematic reviews and meta-analyses and guideline development. [12][13][14][15][16][17][18][19][20][21][22] The pilot version was developed based on common concerns regarding study quality as encountered by physicians and raters who review such literature. The pilot tool consisted of 10 questions.…”
Section: Pilot Versionmentioning
confidence: 99%
“…Without treatment, 10% of people will be at risk for esophageal adenocarcinoma. 14,15 There are also contradictions and disputes in various research conclusions.…”
Section: Introductionmentioning
confidence: 99%